Optimal sequencing of locoregional and systemic therapies for intermediate and advanced hepatocellular carcinoma: a network meta-analysis - Wei Lu; Zhiyuan Li; Chen Pan; Bingliang Chen; Gang Zhang; Zhiming Yang; Jingcheng Hao (Journal of Cancer Research and Clinical Oncology, 2025)
Abstract Introduction Transarterial chemoembolization (TACE), anti-angiogenic drugs (AADs), and immune checkpoint inhibitors (ICIs) are common therapies for hepatocellular carcinoma (HCC). Despite proven benefits of combined regimens, optimal sequencing remains unclear. This network meta-analysis evaluates safety and efficacy of therapeutic sequences in intermediate-advanced HCC. Methods We conducted a comprehensive search of multiple databases, including PubMed, Cochrane Library, Web of Science, and EMBASE, for studies published until February 1, 2025. Cochrane's tools and the Newcastle–Ottawa Scale were used to assess the evaluation of bias. We performed data compilation and conducted a network meta-analysis to compare the relative efficacy of different treatments. Results A total of 56 studies (10,456 patients) evaluated 11 therapeutic sequences. Survival outcomes favored TACE-AADs-ICIs (TAI), which ranked highest for overall survival (OS: SUCRA 90.0%) and progression-free survival (PFS: SUCRA 91.3%). Tumor responses differed significantly across regimens: TACE-ICIs (TI) achieved the highest probability of complete response rate (CRR: SUCRA 83.9%), while AADs-ICIs-TACE (AIT) ranked first in objective response rate (ORR: SUCRA 85.8%). Notably, ICIs-AADs (IA) achieved superior disease control rate (DCR: SUCRA 88.1%). ICIs monotherapy (I) was associated with the lowest incidence of grade ≥ 3 adverse events (AEs: SUCRA 11.7%). Conclusion Our comprehensive network meta-analysis establishes a multidimensional efficacy-safety profile for sequential therapies in intermediate and advanced HCC management. TACE-initiated sequences (TAI/TIA) optimize survival (OS/PFS: SUCRA > 90%), while systemic-first regimens (AIT/IA) maximize tumor response (ORR/DCR: SUCRA > 85%). ICIs monotherapy exhibits the safest profile. Further clinical studies are warranted to determine optimal treatment sequencing for intermediate and advanced HCC.